Activational effects of sex hormones on laterality of 2D vs. 3D mental rotation tasks - Hromatko, Ivana (2014)
Introduction and aim: Previous research suggests that (a) activational effects of sex hormones on gender-biased spatial tasks might be related to hormonally induced changes in laterality, and (b) women use different cognitive strategies when solving 2D vs. 3D mental rotation tasks. The aim of this study was to compare the EEG laterality scores for 2D and 3D mental rotation tasks in early follicular and mid-luteal phases of menstrual cycle, characterized by low vs. high levels of sex hormones. Method: 39 healthy, right- handed female participants were tested in both phases by 2D and 3D versions of spatial tasks. EEG was recorded by a Nihon Kohden electroencephalograph with electrodes placed according to the international 10-20 system. Separate laterality scores (lnR–lnL) were calculated for lower and higher alpha frequency bands at parietal locations. Results: Significant changes within the higher alpha band as a function of menstrual cycle were found for both types of mental rotation tasks, with higher functional asymmetries in early follicular phase. In the lower alpha band the functional asymmetry changed across the cycle for the 3D tasks, with greater right hemisphere activation for 3D tasks, and greater left hemisphere activation for 2D tasks. Conclusion: This set of findings confirms some earlier reported differences in cognitive strategies women use when dealing with 3D vs. 2D objects, but also provides new evidence that changes in functional hemispheric asymmetry across menstrual cycle might be an underlying mechanism in the previously observed activational effects of sex hormones on various cognitive abilities.